Analysis and performance evaluation of new coding options for space telecommand links – part II: jamming channels. (8th September 2014) - Baldi, M.; Chiaraluce, F.; Garello, R.; Maturo, N.; Aguilar Sanchez, I.; Cioni, S.
Summary In this paper, we study the performance of telecommand space links affected by pulsed, continuous wave and pseudo‐noise jamming. Countermeasures include coding, interleaving, and direct sequence spread spectrum. Binary and non‐binary low‐density parity‐check codes, parallel turbo codes, and soft‐decision decoded BCH codes are considered. We investigate the impact of different decoding algorithms, also taking into account the role of jamming state information, spreading processing gain and interleaving. The results show that significant gains (up to more than 10 dB) can be achieved in a number of interesting scenarios. Copyright © 2014 John Wiley & Sons, Ltd.